Pelatihan Manajemen Komprehensif Usaha Kuliner Komunitas Food Truck Bali - Gede Dana Pramitha; Ayu Siska Wulantari; Kurniawan Widiartha (Jurnal Pengabdian Pada Masyarakat, 2022)
COMPREHENSIVE MANAGEMENT TRAINING FOR THE CULINARY BUSINESS OF THE BALI FOOD TRUCK COMMUNITY. Nowadays, the development of micro, small and medium enterprises in Bali is very rapid. More and more people are trying various business opportunities that exist to improve their welfare. Especially during the Covid-19 pandemic, many culinary business actors have sprung up as a solution to survive in an increasingly difficult economic situation. To run well, sometimes there are many problems faced in the development of these businesses. Based on the results of interviews and field observations of culinary business actors, especially in the form of food truck displays, it turns out that not all small business actors/executors use and master management comprehensively for business performance solutions and the use of information technology. And for the training on comprehensive management of the culinary business for 20 members of the Bali Food Truck Community, which is packaged in several materials, namely management, accounting, taxation and a touch of information technology in general, it can be understood well.